2014
DOI: 10.1136/jmedgenet-2014-102348
|View full text |Cite
|
Sign up to set email alerts
|

HLA alleles as biomarkers of high-titre neutralising antibodies to interferon-β therapy in multiple sclerosis

Abstract: 50% of the studied MS patients carried some of the five independently associated HLA allele/allele combinations described in this work. This relevant percentage of patients could benefit a therapeutic decision.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 37 publications
1
9
2
Order By: Relevance
“…Notably, part of the side effect could be explained by the higher production of neutralizing antibodies against drugs (or their metabolites) in the HLA-DRB1*07 : 01 and/or DQA1*02 carriers [59, 60]. Although drug-specific antibodies are undesirable in therapies involving biological proteins, these findings reinforce our results of a much higher frequency and persistence of DBPII neutralizing antibodies in individuals harboring those alleles HLA class II.…”
Section: Discussionsupporting
confidence: 81%
“…Notably, part of the side effect could be explained by the higher production of neutralizing antibodies against drugs (or their metabolites) in the HLA-DRB1*07 : 01 and/or DQA1*02 carriers [59, 60]. Although drug-specific antibodies are undesirable in therapies involving biological proteins, these findings reinforce our results of a much higher frequency and persistence of DBPII neutralizing antibodies in individuals harboring those alleles HLA class II.…”
Section: Discussionsupporting
confidence: 81%
“…In addition, an association of HLA-DRB1*07:01 with ADAs was described for 39 American patients 17 . A study conducted on 610 Spanish patients reported an increased risk of developing NAbs for the combined presence of the haplotype HLA-DRB1*07:01 with the HLA class I alleles HLA-A*26 and HLA-B* 14 and replicated the association of DRB1*04:01 18 . In a Swedish analysis, the HLA-DRB1*15 and HLA-DQA1*05 alleles were associated with an increased risk for developing NAbs in patients treated with interferon β-1a 19 , while HLA-DRB1*04 was nominally associated in patients receiving interferon β-1b.…”
Section: Introductionmentioning
confidence: 85%
“…Although the immunogenicity of biopharmaceuticals is a known critical phenomenon, reasons for the large inter-individual variation in the occurrence of ADA are still poorly understood. In previous studies, nine HLA-DRB1 alleles and two SNPs have been proposed to either influence the risk to develop antiinterferon β antibodies or to be associated with ADA titers [15][16][17][18][19][20] . Six of these markers are assumed to increase the risk for ADA development, the remaining five are candidates for protection from ADA.…”
Section: Discussionmentioning
confidence: 99%
“… 13 15 Smoking is a risk factor for the development of multiple sclerosis (MS), and the risk is greater if smoking is combined with well-known HLA associations. It is also a risk factor for the development of ADAs in IFN-β- and natalizumab-treated MS patients, 16 , 17 as well as for the development of RA by means of a mechanism of citrullination.…”
Section: Discussionmentioning
confidence: 99%